Developing curricula for english for Occupational Purposes: A case study at a South African University of Technology - Rautenbach, E.; Mann, C.C.; van Ryneveld, L. (South African Journal of Higher Education, 2018)
The demand for English for Occupational Purposes (EOP) is growing proportionally to the universal demand for employees, who can function in the lingua franca, English, in their fields of specialisation. Therefore, the training of students at universities of technology, which aim to produce graduates who can perform successfully upon entry into the occupational world, should include the teaching and learning of EOP. This study set out to determine how best to develop EOP curricula, using wants and needs analyses, including all stakeholders at a university of technology, and adopting a case study approach. There was particular focus on: the students, since EOP is learner-centred; the authenticity of learning materials per field of specialisation; and, collaboration between language services-rendering and language services-requesting departments. The main conclusions drawn were that English proficiency plays a central role in the success of learning EOP, and direct feedback from industry on student wants and needs emerged as essential in curriculum planning.